Analisis Tingkat Kesehatan Bank Syariah Menghadapi Pandemi Covid-19 - Fika Azmi; Nugroho Heri Pramono; Mirasanti Wahyuni (Jurnal Ilmiah Ekonomi Islam, 2021)
The COVID-19 pandemic that is hitting the world today has affected industrial sectors, including the banking industry in Indonesia. Even though there is policy protection from the government so that banks can run well, it is not a guarantee that banks will be able to withstand economic shocks. This study aims to examine whether there are differences in the soundness of Islamic banking before and during the COVID-19 pandemic. The variables studied were Risk Profile, Good Corporate Governance, Profitability and Capital. The sample in this study is 42 data from quarterly reports of Islamic banking in Indonesia registered by Otoritas Jasa Keuangan in 2019 and 2020. The data analysis method uses the Paired Sample T-Test and the Wilcoxon Signed Rank Test. The results showed that there was no difference the Risk Profile and Good Corporate Governance between before and during the covid-19 pandemic. Meanwhile, Profitability and Capital have significant differences between before and during the COVID-19 pandemic.